Diagnostic value of biopsy sampling in predicting histology in patients with diffuse malignant pleural mesothelioma. Issue 23 (7th August 2019) - Chirieac, Lucian R.; Hung, Yin P.; Foo, Wai Chin; Hofer, Matthias D.; VanderLaan, Paul A.; Richards, William G.; Sugarbaker, David J.; Bueno, Raphael
Abstract : Background: The classification of diffuse malignant mesothelioma into epithelioid, biphasic, and sarcomatoid types is based on histologic patterns. The diagnosis is made on biopsies, and because of intratumoral heterogeneity, they may not be representative of the entire tumor. The number and volume of biopsies needed to reach diagnostic accuracy in diffuse malignant mesothelioma and their prognostic value remain unclear. Methods: This study examined 759 consecutive patients with pleural diffuse malignant mesothelioma treated by pleurectomy/decortication or extrapleural pneumonectomy for the presence of epithelioid and/or sarcomatoid histology and classified both the presurgery biopsies (core‐needle or thoracoscopic) and surgical resection specimens. The number and volume of biopsies were correlated with pre‐ and postsurgery histologies and overall survival. Results: Diffuse malignant mesothelioma was classified as epithelioid (76%), biphasic (18%), sarcomatoid (5%), or indeterminate (1%) in biopsies and as epithelioid (64%), biphasic (32%), and sarcomatoid (4%) in surgical resection specimens (overall concordance, 80.6%). The positive likelihood ratios were 2.4, 13.6, and 90.1 for biopsies with epithelioid, biphasic, and sarcomatoid histologies, respectively. Concordant histologies between biopsies and resections were associated with a higher number of biopsies (median tissue blocks for concordant histologies vs discordant histologies, 3 vs 2; P < .002) but were less associated with a higher volume (median, 1.2 vs 1.1 cm 3 ; P = .06). In a multivariate analysis, overall survival was independently predicted by histology in the resection specimen ( P < .0001) but not in the biopsy ( P = .09). Conclusions: In contrast to epithelioid histology, sarcomatoid histology in biopsies is highly accurate. Despite intratumoral heterogeneity, the accuracy of histologic classification increases with the number of tissue blocks examined, emphasizing the diagnostic value of extensive sampling by presurgery biopsies. Abstract : Because of intratumoral heterogeneity, the histologic classification of diffuse malignant pleural mesothelioma based on initial biopsies has an accuracy of approximately 80%, particularly with respect to epithelioid histology. According to a large study examining both presurgery biopsies and surgical resection specimens from 759 patients with malignant mesothelioma, initial thoracoscopic biopsies that have concordant diagnoses with surgical resections are sampled with a median of 3 tissue blocks.